Adaptation of Migrant Communities in Kampung Inggris: Communication and Efforts to Prevent Disintegration - Sholihin, Muhammad Anas; Rifa'i, Akhmad (Asketik: Jurnal Agama dan Perubahan Sosial, 2025)
This study aims to explain the communication patterns used by both migrant and local communities, as well as the efforts made to reduce the potential for social disintegration in Kampung Inggris, located in Dusun Tulungrejo, Pare District, Kediri Regency, East Java. Dusun Tulungrejo is known as a center for foreign language learning that attracts people from various regions across Indonesia, bringing with them diverse ethnic, religious, cultural, and linguistic backgrounds. This phenomenon produces a dual impact: on one hand, it offers economic benefits for the local population, but on the other, it presents the risk of social conflict due to differences in cultural values and norms. The study employs a sociological approach based on structural functionalism, as proposed by Talcott Parsons, using the AGIL theory (Adaptation, Goal Attainment, Integration, and Latency) to understand the processes of adaptation and integration within a multicultural society. A qualitative method was used, with data collected through in-depth interviews, documentation, and field observation. The findings indicate that several forms of communication play a significant role in preventing social disintegration, namely interpersonal communication, group communication, and mass communication. Additionally, various social activities—such as village meetings, mutual aid for funerals (kerukunan kematian), group exercise sessions, and communal work (kerja bakti)—serve as key platforms for interaction and integration between local residents and migrants. This research is expected to serve as a foundation for fostering harmonious and sustainable communication between the two groups, while strengthening social integration within the Kampung Inggris community.